Introduction to water resources and environmental issues - Pennington, Karrie Lynn.; Cech, Thomas V. (New York : Cambridge University Press, 2010)
'How much water does the world need to support growing human populations? What factors influence water quality, droughts, floods, and waterborne diseases? What are the potential effects of climate change on the world's water resources? These questions and more are discussed in this thorough introduction to the complex world of water resources. The strength of the book is its coverage of the fundamentals of the science of water, aquatic ecology, geomorphology and hydrology, supplemented by internet resources and examples from water resource issues in the news to engage the student. The book begins with a short history of human use and influence on water, followed by chapters on the geomorphology, hydrology, chemistry, and biology of lakes, rivers, and wetlands. Major disease issues, worldwide water quality and quantity problems, and potential solutions are addressed. Water laws, water allocation, and the conflicts involved are discussed using US and international examples. Students in departments of environmental studies, life science, Earth science, and engineering will benefit from this broad survey of these crucial issues'--Provided by publisher.
'The book begins with a short history of human use of and influence on water. The basics of water chemistry and the hydrologic cycle are discussed in detail, with chapters on the geomorphology, hydrology, chemistry, and biology of lakes, rivers, and wetlands. Major disease issues, worldwide water quality and quantity problems, and potential solutions are also addressed'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Water; Hydrologic cycle; Water conservation